Assistance in PIRT registration and halal certification for home industry Jenang Lot Karyasari, Bojong, Magelang Regency - Dakum Dakum; Mura Aristina; Yusuf Fatoni; Amiyati Amiyati; Astuty Wahyuningsih; Rani Setiawati (Universitas Muhammadiyah Magelang, 2022)
A traditional home industrial product called Jenang Lot Karyasari can be found in Bojong Hamlet, Mungkid District, and Magelang Regency. Although the home industry has been operated about 20 years, the production and marketing procedures are still traditional. Additionally, they lack a PIRT license and a halal certification. This service project's goals are to socialize and assist the MSME with PIRT registration and halal certification. Mentoring and counseling are the techniques employed. As a result, partners can comprehend and register for PIRT and halal certification. Similar activities must be carried out in the future to help players in the home industry get product legality and boost their sales potential.